ANALISIS PENDAPATAN USAHATANI RUMPUT LAUT DI DESA TINDAKI KECAMATAN PARIGI SELATAN KABUPATEN PARIGI MOUTONG - Setiawan, Mohammad Rizky; Tangkesalu, Dance; Sulmi, Sulmi (Fakultas Pertanian, Universitas Tadulako, 2024)
Seaweed (Gracilaria sp.) serves as both a valuable source of foreign exchange and a significant income stream for coastal communities. Given the expansive maritime resources available, the development of seaweed farming presents a lucrative opportunity for these communities. This study was conducted to assess the income levels of seaweed farmers in Tindaki Village, South Parigi Subdistrict, Parigi Moutong District. The research took place from June to September 2022. A census method was employed to select respondents, encompassing all individuals within the population, which consisted of 30 seaweed farmers. The analysis revealed that the average production per farmer was 519.7 kg, with a selling price of IDR 21,000 per kilogram. The total revenue generated was IDR 10,938,900, against total costs of IDR 6,166,167. Consequently, the average annual income for seaweed farmers in Tindaki Village was IDR 7,591,333. These findings highlight the economic significance of seaweed farming in this region.